Hollow-polydopamine-nanocarrier-based near-infrared-light/pH-responsive drug delivery system for diffuse alveolar hemorrhage treatment - Zhang, Lingyan; Li, Mifang; Wang, Yeying; Liu, Yibiao; Zhang, Feiyuan; Lin, Zhihao; Zhang, Yuling; Ma, Mingliang; Wang, Shouju (Frontiers in Chemistry, 2023)
Diffuse alveolar hemorrhage (DAH) is a serious complication caused by systemic lupus erythematosus (SLE). Tissue damage and changes in immune response are all associated with excessive free radical pro-duction. Therefore, removing excess reactive oxygen species (ROS) are considered a feasible scheme for DAH treatment. Cyclophosphamide is often used as the main therapeutic drug in clinics. However, CTX carries a high risk of dose-increasing toxicity, treatment intolerance, and high recurrence rate. The combi-nation of therapeutic drugs and functional nanocarriers may provide an effective solution. PDA is rich in phenolic groups, which can remove the ROS generated in inflammatory reactions, and can serve as excel-lent free radical scavengers. Here, we developed a hollow polydopamine (HPDA) nanocarrier loaded with CTX by ionization to prepare the novel nanoplatform, CTX@HPDA, for DAH treatment. Material tests showed that the CTX@HPDA nanoplatform had a uniform diameter and could release CTX in acidic envi-ronments. The vitro experiments demonstrated that CTX@HPDA has good photothermal conversion abil-ity and photothermal stability. Animal experiments demonstrated that the CTX@HPDA nanoplatform had good biocompatibility. The nanoplatform can dissociate in acidic SLE environment and trigger CTX re-lease through photothermal conversion. Combining HPDA, which scavenges oxygen free radicals, and CTX, which has immunosuppressive effect, can treat pulmonary hemorrhage in SLE. Micro-CT can be used to continuously analyze DAH severity and lung changes in mice after treatment. The pulmonary exu-dation in the various treatment groups improved to varying degrees. CTX@HPDA is a simple and efficient nanocarrier system for DAH therapy. This work provides valuable insights into SLE treatment.